Exhaustive Exercise-Induced Cardiac Conduction System Injury and Changes of cTnT and Cx43 - Chang, Y.; Yu, T.; Yang, H.; Peng, Z. (International Journal of Sports Medicine, 2015)
Up to now, studies of exercise-induced cardiac arrhythmia have focused primarily on the working myocardium, with few studies examining to the cardiac conduction system where the rhythmic and synchronized contraction of the heart is initiated. To explore whether the cardiac conduction system is involved in the exercise-induced cardiac injury, we performed histological analysis of sinoatrial node, atrioventricular node and Purkinje fibers and tested the level of structural protein cardiac troponin T and Connexin 43 in Sprague Dawley rats following repeated exhaustive exercise. We found increased collagen deposition, hyperplasia interstitialis, and enhanced activity of lactate dehydrongenase and acid phosphatase in the cardiac conduction system following repeated exhaustive exercise. Mitochondrial alterations, enlarged area of intercalated disc and disappearance of gap junctions were additionally observed through electron transmission microscopy. In addition, significant decreases in cardiac troponin T and Connexin 43 were present in the cardiac conduction system in response to repeated exhaustive exercise. All of these findings demonstrate that repeated exhaustive exercise induces ischemic alterations, damage to cytoskeleton and gap junctions, and tissue fibrosis in the cardiac conduction system in rats. These data may shed a new light on the mechanism of exercised-induced cardiac injury and arrhythmia.
Keywords: repeated exhaustive exercise; cardiac conduction system; exercise-induced arrhythmia; cardiac troponin T; connexin 43